2021
DOI: 10.1101/2021.11.30.21267089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual risk among pregnant women at risk of HIV infection in Cape Town, South Africa: What does alcohol have to do with it?

Abstract: This study examines associations between alcohol use and HIV sexual risk among a cohort of HIV-uninfected pregnant women (n=1201) residing in a high HIV burden community in South Africa. Alcohol use was measured using a modified version of the Alcohol Use Disorder Identification Test (AUDIT). HIV sexual risk was measured through a composite variable of four risk factors: diagnosis with a STI, self-report of >1 recent sex partners, partner HIV serostatus (unknown or HIV+) and condomless sex at last sex. Any … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, our recently published study using baseline data from the same study found that pregnant women reporting any alcohol use in the year before pregnancy had greater odds of being at high risk of HIV (aOR 1.33, 95% CI: 1.05-1.68), using a proxy measure that consisted of several sexual HIV risk factors, which included awareness of partner HIV status (as well as presence of an STI, multiple sexual partners, and condom use). 7 In this study, alcohol use before pregnancy was associated with higher perceived risk of HIV acquisition. Pregnant women who use alcohol may thus recognize that they are at increased risk of HIV because of other sexual risk behaviors and therefore be more likely to adopt PrEP as their preferred prevention strategy and adhere to it well.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…However, our recently published study using baseline data from the same study found that pregnant women reporting any alcohol use in the year before pregnancy had greater odds of being at high risk of HIV (aOR 1.33, 95% CI: 1.05-1.68), using a proxy measure that consisted of several sexual HIV risk factors, which included awareness of partner HIV status (as well as presence of an STI, multiple sexual partners, and condom use). 7 In this study, alcohol use before pregnancy was associated with higher perceived risk of HIV acquisition. Pregnant women who use alcohol may thus recognize that they are at increased risk of HIV because of other sexual risk behaviors and therefore be more likely to adopt PrEP as their preferred prevention strategy and adhere to it well.…”
Section: Discussionmentioning
confidence: 57%
“…Although our study collected data on alcohol use since learning one was pregnant, we used measures of any alcohol use and hazardous alcohol use in the past year before pregnancy as our exposure variables of interest. We report past year alcohol use before pregnancy for several reasons: (1) consistency with our previous sensitivity analysis of alcohol use measures among pregnant women, 7 (2) sensitivity analysis in the present analysis of women who reported continued alcohol use in the sample at 3-month follow-up which was very small (5%), (3) the high potential for underreporting alcohol use while pregnant because of social desirability bias, (4) additional previous work suggesting that alcohol use before pregnancy is a good predictor of continued alcohol use during pregnancy, 26 and (5) the late median gestational age at first antenatal care visit of 21 weeks (the fifth month of pregnancy) and high prevalence of unplanned pregnancies reported in previous analyses of this cohort, both of which suggest participants were unaware they were pregnant for several months of the pregnancy and may have continued drinking during this time. 27 The Alcohol Use Disorders Identification Test—Consumption (AUDIT-C) 28 was used to measure recalled and self-reported alcohol use in the year before pregnancy (range 0–12).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations